Comparison Method Of Cutting Honeycomb Core - Hashim, Muhammad Reduan (Universiti Sains Malaysia, 2017)
The aim of this project is to determine the method for cutting honeycomb core without need any additional process with zero defect, and to compare the cutting quality with another method of cutting. In this project laser cut, milling cutters, and hot wire cutting method is preferred to cut the nomex honeycomb core, polypropylene honeycomb core, and thermoplastic honeycomb core. This study is seeking better ways to producing smooth cutting finish when cutting the nomex honeycomb core. This study represents the method of cutting of nomex honeycomb core with various parameters such as power, time, speed and thickness of the specimen. The results shows that using 5 watt of laser cut, it produces better surface finish without many burr produced, compared using milling cut but, there have burn spot that can be smooth up by sand paper. For hot wire cutting result, it shows smooth surface finish with less material wasted for material polypropylene and thermoplastic honeycomb core, but it has a problems with nomex honeycomb core due to less energy of power supply. For this experiment, the hot wire was used dry cell as their power supply so it cannot cut the nomex honeycomb core due to properties in nomex material and less power consumption. Overall, using 5 watt laser machine are suitable for cutting honeycomb core, because the focal point of laser need to be adjusted in getting the smallest diameter of focal length due to thickness of materials. Lastly, laser cutting method are able to cut nomex honeycomb core, and it can be the best method for cutting nomex materials if it was using carbon dioxide laser type to cut nomex honeycomb core.